LEGAL CERTAINTY REGARDING COLLECTION RELATED TO GUARANTEES IN TERMS OF MOTOR VEHICLE FINANCING BASED ON OJK REGULATION NO. 22 OF 2023 - Purba, Kevin Agatha; Harjono, Dhaniswara K.; Panjaitan, Hulman (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2024)
One form of law that has a real and important role in people's lives is contract law. The term